IMPLEMENTASI PERMAINAN TRADISIONAL DHAKON TERHADAP PERKEMBANGAN KOGNITIF DAN SOSIAL EMOSIONAL ANAK DI TAMAN KANAK-KANAK PERTIWI DESA TEGAL ARUM KECAMATAN RIMBO BUJANG KABUPATEN TEBO PROVINSI JAMBI - Farida; Dodi Harianto (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to determine the implementation of the traditional dhakon game and its impact on the cognitive and social-emotional development of early childhood at TK Pertiwi 5B. The main problem underlying this research is the low concentration of children, lack of basic counting skills, and the high level of egocentrism due to excessive smartphone use at home. The approach used in this study is descriptive qualitative with field research methods. The research subjects consisted of the Principal, classroom teachers, and 15 children of Group B at TK Pertiwi 5B. Data collection techniques were carried out purely through direct observation and in-depth interviews. Data analysis used the Miles and Huberman model, while data validity was tested using source triangulation. The results showed that the consistent implementation of the traditional dhakon game was proven to be highly effective in shifting children's dependence on smartphones and providing balanced stimulation. Children's development experienced a significant increase, where they are now able to recognize number symbols in a fun way, become more focused, honest, orderly queue waiting for their turn, and control emotions by accepting defeat gracefully. In conclusion, habituation through concrete traditional game media can effectively shape children's logical thinking and positive character from an early age.